Psittacine Feather and Beak Disease Testing and DNA Sexing of Wild Red-Vented Cockatoo Chicks at Rasa Island, Palawan - Rebong, Glenn; Boussesky, Marc; Widdman, Peter; Lacerna, Indira D.; Diaz, Siegfred H. (Silliman Journal, 2022)
The Philippine Cockatoo or Red-vented Cockatoo (Cacatua haematuropygia) is a critically endangered bird endemic to the country. Habitat destruction, extermination, poaching for the pet market, and potential diseases caused by the introduction of captive birds in wild populations were cited as the reasons for the decline. One of projects of the Philippine Cockatoo Conservation Program is to determine if the wild population in Rasa Island carries the Psittacine Beak and Feather Disease (PBFD) virus. Blood and feather samples were collected and sent to a laboratory for the PBFD test and DNA sexing. Sixteen birds were ringed. Fifteen feather samples and six blood samples were collected and cent to France for PBFD test and DNA sexing. Among the 15 birds, eight cockatoo chicks ?were male and four were females. Two cockatoos were not tested due to insufficient samples and one had no result. Physical examination and blood testing showed that most of the cockatoo chicks sampled were apparently healthy and did not carry the PBFD virus.